Credit Plan (1980-82) and Action Plan (1980) for Rangareddy District Andhra Pradesh - Planning Commission (Planning Commission, 1980)
There is no gainsaying the fact that the District Credit Plan, if implemented successfully, will carry the district forward in its much needed economic growth, with particular emphasis on removal of unemployment/ underemployment, raising the standard of living of the poorest section of the people, provision of basic needs to the weaker sections, boosting the production in the agricultural and industrial sectors etc.
State Bank of Hyderabad